Graphene oxide-supported β-tin telluride composite for sodium- and lithium-ion battery anodes - Grishanov, Dmitry A. (2020)
High‐charge‐capacity sodium‐ and lithium‐ion battery anodes based on tin telluride are reported for the first time. Graphene oxide/cubic β‐SnTe electrodes exhibit exceptionally high reversible volumetric charge capacities above 3000 and 1300 mAh cm−3 at 100 mA g−1 charging rate for lithium and sodium ion batteries, respectively, and they show very good rate capabilities retaining 68 and 60 % of the respective capacities even at 2000 mA g−1 charging rate. The reversible charge capacity for lithiation is approximately equal to the theoretical value of the active material. The superior electrode performance is attributed to the high conductivity of tellurium, the mechanical buffering of volume changes by the large row‐V host elements, the elasticity of the reduced graphene oxide support, and the very low specific equivalent volumes involved in sodiation and lithiation of SnTe.